2003
DOI: 10.1080/j.1600-0455.2003.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and histopathologic changes in the bowel after super-selective transcatheter embolization for focal lower gastrointestinal hemorrhage

Abstract: Purpose: To evaluate the safety of superselective arterial embolization therapy in the lower gastrointestinal tract. The sequelae on normal enteric tissue in lower gastrointestinal arterial embolization were retrospectively reviewed.Material and Methods: To control hemorrhage and tumor blood supply, 14 patients were treated by superselective transcatheter embolization at different levels of the colonic and small intestine vessels via the superior and inferior mesenteric arteries using microcoils and/or gelatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The coaxial microcatheter system has made it possible to catheterize the branches superselectively, and microcoils can be placed easily and accurately for permanent occlusion. 7,8 In our case, the marginal artery distal to the pseudoaneurysm was disrupted by vascular injury. Thus, we succeeded in occluding the pseudoaneurysm only by proximal embolization.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The coaxial microcatheter system has made it possible to catheterize the branches superselectively, and microcoils can be placed easily and accurately for permanent occlusion. 7,8 In our case, the marginal artery distal to the pseudoaneurysm was disrupted by vascular injury. Thus, we succeeded in occluding the pseudoaneurysm only by proximal embolization.…”
Section: Discussionmentioning
confidence: 83%
“…Horiguchi et al 8 reported that there were no mucosal ischemic changes on colonoscopy after embolization with microcoils at the marginal artery (or in the present case) for lower gastrointestinal bleeding in fi ve cases. Although it is rare, delayed bowel stenosis due to ischemic change is observed after blunt abdominal trauma treated by conservative management.…”
Section: Discussionmentioning
confidence: 84%
“…The success rate is 81%-93% and the mortality rate, 0%-7%. 4,[6][7][8] Crohn's disease is a transmural inflammatory disease of unknown origin. Although primarily managed medically, 70% to 90% of patients will require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to adjust the ratio to the length of the segment to be occluded, as performed in the present study (1). Thus, the mixture has sufficient low viscosity to allow distal embolization of the feeding artery but at the same time it is viscous enough to prevent the embolic agent from propagating too far into the capillary bed, preserving circulation in the distal post-embolic tissue via collateral channels in the intramural microcirculation (4,5). NBCA/lipiodol has several other advantages.…”
Section: To the Editormentioning
confidence: 95%